Accuracy of Three‐Dimensional Printed Templates for Guided Implant Placement Based on Matching a Surface Scan with CBCT. (28th April 2015) - Kernen, Florian; Benic, Goran I.; Payer, Michael; Schär, Alex; Müller‐Gerbl, Magdalena; Filippi, Andreas; Kühl, Sebastian
Abstract: Background: Reference elements are necessary to transfer a virtual planning into reality for guided implant placement. New systems allow matching optical scans with three‐dimensional radiographic images. Purpose: To test whether digitally designed three‐dimensional printed templates (D‐temp) fabricated by matching surface scans and cone beam computed tomography (CBCT) images differ from the templates fabricated in‐lab (L‐temp) by using a physical transfer device for the positioning of the guiding sleeves. Materials and Methods: L‐temp were fabricated for eight human lower cadaver‐jaws applying a digital planning software program (smop, Swissmeda AG, Zürich, Switzerland) using a Lego® (Lego Group, KIRKBI A/S, Billund, Denmark) brick as reference element and the respective transfer device (X1‐table). Additionally, digital templates (D‐temp) using the identical planning data sets and software were virtually designed and three‐dimensional printed, after matching a surface scan with CBCT data. The accuracy of both templates for each planning was evaluated determining the estimated coronal, apical, and angular deviation if templates were used for implant placement. Results: Mean coronal deviations for L‐temp were 0.31 mm (mesial/distal), 0.32 mm (lingual/buccal), and 0.16 mm and 0.23 mm for D‐temp, respectively. The mean apical deviations for L‐temp were 0.50 mm (mesial/distal), 0.50 mm (lingual/buccal). and 0.25 mm and 0.34 mm for the D‐temp, respectively. Differences between both devices were statistically significant ( p < .05). Conclusions: A higher accuracy of implant placement can be achieved by using three‐dimensional printed templates produced by matching a surface scan and CBCT as compared with templates which use physical elements transferring the virtual planning into reality.